Penatalaksanaan Fisioterapi Menggunakan Foot Core Strengthening Exercise Untuk Meningkatkan Aktifitas Fungsional Pada Kasus Plantar Facitis - WANTI wanti HASMAR; Faridah Faridah (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2021)
ABSTRACT Background : Plantar Fascitis is inflammation of the plantar fascia Excessive stretching of the plantar fascia can result in a tear and then cause irritation to the plantar fascia, weakness of the intrinsic muscles of the foot, weight gain or strenuous activity, it causes a pull on the plantar fascia, This results in tearing and irritation of the plantar fascia. Plantar fasciitis patients have functional activity disorders so the patient must be given proper management, one of which is using foot core strengthening. This study aims to determine the management of foot core strengthening in increasing functional activity in plantar fasciitis cases. The method used is a case study method with 1 respondent using a Jette scale measuring instrument to measure functional activity. The results of a study conducted in Kota Baru Subdistrict, Jambi City, showed that foot core strengthening for 12 times of therapy in 4 weeks could improve the functional activity of plantar fasciitis patients. The conclusion of this study is that foot core stretching can increase the functional activity of plantar fasciitis patients because this exercise can increase muscle strength and intrinsic muscle endurance in the feet, when the intrinsic muscles are strong the plantar fascia does not work hard so that there is a decrease in inflammation in the plantar fascia so that it can increase activity. functional. Keywords: Plantar fasciitis, foot core strengthening, jette scale.